An overview of Ethnomedicinal plants of Uzbekistan - Khojimatov, Olim Kahharovich; Khamraeva, Dilovar Tolidjonovna; Khujanov, Alisher Nuralievich; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2020)
Background: The Flora of Central Asia is extremely rich, with about 9800 species of vascular plants. Uzbekistan, with over 4500 species, has a central position in the region, and is regarded as one of the main centers of medicinal plants diversity, in particular because of its high percentage of local endemism. About 600 species of medicinal plants have been documented in Uzbekistan for the treatment of numerous diseases, many of them endemic. These plants are still used for the medicinal traits in industrial scale as well as by local tabibs (local practitioner). Methods: During research, semi-structured interviews were conducted with tabibs, elders and herders with experience in healing by using medicinal plants. During expedition visits, herbarium material and samples of medicines from vegetative raw materials were collected. Collected materials were determined using local floristic monographs and herbarium vouchers. Results: During fieldwork, we recorded 117 medicinal plants belonging to 45 families and 94 genera, used widely for the treatment of various diseases. Traditional practitioners prepared the plants mostly as extract, decoction, powder, bathing and sometimes used them fresh. Extract and decoction were generally preferred, and the preparations were normally made fresh just before use. Some of the encountered plants are now also used by private entrepreneurs for the production of herbal medicines for various purposes. Conclusions: Our results show that despite the achievements of modern allopathic medicine, the population in Uzbekistan continues to actively use wild medicinal plants for health purposes. The wide availability of medicinal plants, low costs, and perceived efficacy contribute to popularization of traditional medicine. Keywords: Ethnobotany; ethnopharmacology; medicinal plants; Uzbekistan; Central Asia.